SASI IKAN LOMPA SEBAGAI PENDEKATAN PENDAMPINGAN BERBASIS BUDAYA DALAM UPAYA REKONSILIASI DAN KEBERLANJUTAN HIDUP BERSAMA DI PULAU HARUKU-MALUKU - Sohilait, Marce; Tampake, Tony; Lauterboom, Mariska (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
This article argues the cultural values of sasi ikan lompa as a culture-based mentoring approach. The local culture-based approach is an illustration of a contextual mentoring approach based on local wisdom which is a characteristic of the multicultural Indonesian nation. This research uses a qualitative ethnographic method by obtaining data through observation, interviews, and literature study. The data analysis technique used is through the stages of data reduction, data processing, and conclusion. The research results obtained are first; Lompa fish sasi can be used as culture-based assistance in society because it contains the values of assistance regarding guidance, solidarity, harmony, masohi (cooperation). Second, assistance based on cultural values can create a reconciliation effort for indigenous communities on Haruku Island where conflicts often occur between countries/villages. Third, a culture-based mentoring approach shows the alignment of Indigenous communities towards ecological justice. Apart from that, a culture-based mentoring approach can develop and control the community to prevent the exploitation of nature amidst the threat of an environmental crisis due to global warmingMagister Sosiologi Agama, Fakultas Teologi, Universitas Kristen Satya Wacana